A Literature Review of the Strengths and Limitations of Premarital Preparation: Implications for a Canadian Context - Green, Amy Rose; Miller, Lynn D. (Canadian Journal of Counselling and Psychotherapy, 2013)
The adverse effects of marital dissolution and dissatisfaction point to a need for interventions, such as premarital preparation, to improve marital quality. Although several studies support the potential for premarital preparation to improve couples’ marital satisfaction and interpersonal skills, results from other studies are mixed. Moreover, current research investigating the effectiveness of premarital preparation in a Canadian context is virtually nonexistent. This literature review examines the contributions and limitations of premarital preparation from international research and discusses implications and next steps for Canadian researchers and practitioners.